2019
DOI: 10.3390/biom9120888
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products (AGEs) May Be a Striking Link Between Modern Diet and Health

Abstract: The Maillard reaction is a simple but ubiquitous reaction that occurs both in vivo and ex vivo during the cooking or processing of foods under high-temperature conditions, such as baking, frying, or grilling. Glycation of proteins is a post-translational modification that forms temporary adducts, which, on further crosslinking and rearrangement, form permanent residues known as advanced glycation end products (AGEs). Cooking at high temperature results in various food products having high levels of AGEs. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 114 publications
(174 reference statements)
1
119
0
4
Order By: Relevance
“…Typically, CVD including nonfatal myocardial infarction was strongly associated with the development of CKD [33]. Furthermore, the intermediate products of the Maillard reaction and caramelization, such as dicarbonyl compounds, which possibility increased the total body AGEs load [34] which might lead to diabetes, obesity and renal failure [34,35]. We also hypothesized that the acrylamide (ACR), commonly detected in the baked foods, was a risk factor for CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, CVD including nonfatal myocardial infarction was strongly associated with the development of CKD [33]. Furthermore, the intermediate products of the Maillard reaction and caramelization, such as dicarbonyl compounds, which possibility increased the total body AGEs load [34] which might lead to diabetes, obesity and renal failure [34,35]. We also hypothesized that the acrylamide (ACR), commonly detected in the baked foods, was a risk factor for CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study by Avila et al found that red meat was positively relevant to serum ferritin [32], which can increase the risk of NAFLD [33,34]. Fried food will produce some hazardous chemicals, such as advanced glycation end products and trans fatty acids [35,36], which were reported to play a critical role in NAFLD [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…AGEs are a group of glycotoxins produced in reaction of free amino groups of proteins, lipids, or nucleic acids and carbonyl groups of reducing sugars. The AGEs can accumulate in tissues and body fluids, resulting in protein malfunctions, reactive chemical production, and inflammation [ 214 ]. The levels of AGEs were significantly elevated in serum of RRMS patients, but no significant change was observed after IFN-β treatment [ 74 ].…”
Section: Degradation Products Under Oxidative Stressmentioning
confidence: 99%